THE AXIOMS OF SIMULATION MODEL OF MAKING DECISION - Коврижкін, О. Г.; Лагута, А. Г. (Science-based technologies, 2009)
Сonsidered the creation of systems that mimic aspects of human behavior in decision-making process andsynthesizing the structural model of decision making.